Edge-Interior Gradient Effects on the Understorey Bird Community in an Isolated Ayer Hitam Forest Reserve, Malaysia - Moradi, Hossein Varasteh (2009)
The fact that the world is losing its biodiversity due to human activities, particularly around the tropical forest region, has been widely known. One of the biggest threats to biodiversity is the edge effects, especially in isolated and fragmented habitats. Thus, to investigate the edge effects on the community of understorey birds, an isolated tropical rain forest of Malaysia was chosen. The objectives of this study were: (1) to examine the species composition, richness, abundance, and density changes across edge-interior gradient; (2) to detect any distinct bird communities associated with certain habitat types and the factors affecting the association (3) to distinguish the interior and edge specialist species and guilds. The point-count sampling method was used in a 1248-ha lowland rain forest patch of Ayer Hitam Forest Reserve to carry out a survey on the individual understorey bird and species, at each of the 93 survey points, between December 2006 and July 2008 Birds and environmental variables were recorded within a 25 m radius of each point. A total of 2263 observations, 72 species, representing 19 families were recorded in this study. The species composition, density, abundance, and diversity of birds showed some significant differences across the edge-interior gradient at the guild and species levels. Based on the bird-habitat association, along the edge-interior gradient, two groups were distinguished. These were the edge-specialist group which was positively correlated with ground cover, light intensity, shrub cover, temperature, and percentage of shrub cover between 0.5 and 2 m in height; meanwhile the interior-specialist group was highly sensitive to the forest edge and could indicate good habitat quality of forest interior with high humidity, dense canopy cover, high number of dead trees, high percentage of litter cover, and deep litter layer. At the guild level, the results showed that the terrestrial insectivores and sallying insectivores are sensitive to edge and have positive correlation with distance from the edge, leaf litter depth, canopy cover, and the number of tall trees (>10 m). The presence of some species such as the Yellow-vented Bulbul, Cream-vented Bulbul, and Plaintive Cuckoo was associated with high light intensity and shrub cover, which are the best indicators of the edge. Meanwhile, the presence of Short-tailed Babbler, Moustached Babbler, and Black-caped Babbler was associated with high relative humidity and leaf litter cover, which are the best indicators of forest interior. Changes in the micro-environment at the edge are a key factor to indicate the understorey avian responses to the edge-interior gradient. As edge specialists can be widely found in the matrix surrounding the patch, they require less conservation against being declined or endangered; i.e. they can be well managed in the matrix surrounding the forest patches. Interior-specialists, on the other hand, especially terrestrial insectivores, should be given the most attention in conservation of forest areas. From the conservation viewpoint, the forest remnants in the lowlands of Peninsular Malaysia are of considerable concern. Due to the characteristics including thick leaf litter layer, dense canopy cover, high number of dead trees, and high relative humidity, these remnants have the capability of supporting the understorey bird species sensitive to edge effects.